The European Union in International Investment Governance: a Hybrid Approach to Dispute Settlement - Beatriz Pérez de las Heras (Romanian Journal of European Affairs)
Investor-state dispute settlement and arbitration, in particular, stands at the centre of a process intended to reform the global regime of international investment treaties. The mechanism’s negative impact on public decision-making processes and its inherent shortcomings, such as an absence of transparency and a lack of arbitrator independence, have impelled moves to redesign the system. As a leading actor in the international investment landscape, the European Union (EU) has proposed replacing traditional arbitration with a specific court system for each bilateral agreement containing investment arrangements. However, the proposed system retains key aspects of classic arbitration whilst posing as yet unresolved issues in relation to the interaction with the EU Court of Justice and the current institutions of international arbitration. Nevertheless, the EU’s initiative is intended merely as a transitional remedy, ultimately leading to a multilateral judicial institution that would bring greater consistency to the resolution of investment disputes. Though important for the contribution it makes to the current debate, the EU’s proposal has faced criticism for some crucial deficits. Therefore, if the EU’s project is to prosper, it must first be discussed and agreed upon as part of a broader agenda of investment governance reform at a global level.